Terapi Islami Ala Padepokan Iqro’ Terhadap Fenomena Pergaulan Bebas di Desa Kolam Kecamatan Percut Sei Tuan - Septiana, Tiara; Nasution, Muhammad Ali Azmi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
In Kolam Village, the rise of negative behavior among the community and teenagers, especially promiscuity, demands special treatment to protect the younger generation from deviant actions. One approach to dealing with this problem is through religion. This research explores the application of Islamic therapy at Padepokan Iqro' as a solution to overcome the phenomenon of promiscuity. This therapy involves religious practices such as dhikr, prayer, and reading the Koran. Researchers feel it is important to highlight how Padepokan Iqro' applies Islamic therapy in dealing with promiscuity. The method used in this research is qualitative, with data collection techniques through interviews, observation, documentation and literature study. The research results show that the Islamic therapy implemented at Padepokan Iqro' in the form of religious activities such as dhikr, prayer and reading the Koran, aims to help the community, especially teenagers, in reducing social problems such as promiscuity.